Soluble CD14 is a nonspecific marker of monocyte activation. (19th June 2015) - Shive, Carey L.; Jiang, Wei; Anthony, Donald D.; Lederman, Michael M.
Abstract : Soluble CD14 is associated with morbidity and mortality in HIV disease. It is a co-receptor for lipopolysaccharide (LPS) that is released from monocytes upon activation. We demonstrate here, that inflammatory cytokines can induce the release of sCD14 in peripheral blood mononuclear cell cultures from healthy donors, and that TLR ligands other than LPS can cause a decrease in the monocyte cell surface expression of CD14. Thus, sCD14 is a marker of monocyte activation, not restricted to activation by LPS.